PENGARUH PENDEKATAN DEEP LEARNING TERHADAP LITERASI MATEMATIS DAN SELF AWARENESS PESERTA DIDIK - Imelda, Siska; Andriani, Siska; Alhaq, Arini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students’ mathematical literacy and self-awareness remains one of the major challenges in 21st-century mathematics education. This study aimed to examine the effect of the Deep Learning approach on the mathematical literacy and self-awareness of eighth-grade students at SMP Negeri 31 Bandar Lampung. A quantitative approach with a quasi-experimental design was employed. The sample consisted of two classes: Class VIII A as the experimental group, which received Inquiry learning integrated with the Deep Learning approach, and Class VIII B as the control group, which received Inquiry learning using the scientific approach. The research instruments included a mathematical literacy test and a self-awareness questionnaire that had satisfied the validity and reliability requirements. Data were analyzed using Multivariate Analysis of Variance (MANOVA) after meeting the assumptions of normality and homogeneity. The results revealed that the Deep Learning approach had a significant simultaneous effect on students’ mathematical literacy and self-awareness (Wilks’ Lambda, p = 0.000; Partial Eta Squared = 0.547). It also had significant partial effects on mathematical literacy (p = 0.000; Partial Eta Squared = 0.412) and self-awareness (p = 0.000; Partial Eta Squared = 0.272). Furthermore, the experimental group achieved higher mean scores in mathematical literacy (82.66) and self-awareness (74.91) than the control group (70.94 and 66.49, respectively). Therefore, the Deep Learning approach implemented through the Inquiry model is effective in improving students’ mathematical literacy and self-awareness and can be considered an alternative instructional approach that promotes both cognitive and affective development in mathematics learning.